Ion-Sieving Dual-Scale Asymmetric Cellulose Membrane as a Sustainable Paper-Based Separator for Ultra-Stable Zinc Anodes - Liu, Xinlong; Zhang, Junze; Fang, Cuiqin; Xiao, Yana; Yang, Yujue; Wang, Shuai; Yang, Qingjun; Wu, Yaopeng; Xu, Bingang (Nano-Micro Letters, 2026)
Conventional glass fiber separators used in aqueous zinc-ion batteries (ZIBs) are inadequate in suppressing Zn dendrite growth and parasitic reactions due to unregulated ion transport. Here, we design a fully biodegradable and dual-scale asymmetric paper-based membrane that synergistically couples a macroporous paper scaffold with a surface layer of carboxylated nanoporous cellulose nanofibers (CNFs) for ion regulation. This dual-scale architecture establishes coordination-assisted ion-hopping pathways via Zn2+–COOH interactions, homogenizing Zn2+ flux to enable uniform nucleation and inhibit dendrites. Simultaneously, the nanoporous and negatively charged CNF layer functions as an ion sieve, preferentially conducting Zn2+ while restricting water mobility and polyiodide shuttling, thereby mitigating side reactions. When deployed as a separator, the membrane enables an ultra-stable Zn||Zn symmetric cell cycling over 1,900 h at 1.0 mA cm−2 and an average Coulombic efficiency of 97.3% in Zn||Cu cells, achieving a sixfold lifespan extension over commercial glass fiber separators. The corresponding Zn||I2 full cell retains a specific capacity of 172.8 mAh g−1 after 4,000 cycles at 2.0 A g−1, underscoring its efficacy in suppressing shuttle effects. This cellulose-based design reduces separator cost by 83% while ensuring full biodegradability, offering a practical and sustainable pathway toward high-performance ZIBs. Highlights: 1 A cost-effective and fully biodegradable dual-scale paper-based separator is engineered by intertwining macroporous rice paper with mesoporous nanofibers. 2 Nanoporous ion sieving and molecular confined pathways effectively suppress polyiodide shuttling and water-induced side reactions. 3 Regulated ion transport induces a uniform solid-electrolyte interphase, enabling dendrite-free anodes and high Coulombic efficiency.